Design of Medical Diagnostic System Based on Artificial Intelligence - Wang, Yu-Hui; Lin, Guan-Yu (Bright Institute, 2023)
With the progress of science and technology, material life is getting better and better now, so people have begun to have higher and higher requirements for life and longevity has more and more yearning. In ancient times are through artificial diagnosis to find out the physical condition, Chinese medicine is expected to smell cut the four major methods of diagnosis and treatment, but can achieve this skill only a small number of people, and most of the disease can not be identified, not good to treat patients. So now with the progress of science and technology, technology and intelligent rapid development, artificial intelligence may be able to make some contributions to the diagnosis of the disease. Therefore, the purpose of this paper is to design artificial intelligence-based medical diagnostic system to update. In this paper, after identifying the basic structure of artificial intelligence and constructing the database, we understand the diagnosis methods of medical diagnostic system and other diagnostic systems, and finally, the medical diagnostic system can be updated by using the phase-changing algorithm, so that it can better fit with artificial intelligence, so as to ensure the success rate of treatment and the correct rate of diagnosis. Experimental results show that the use of artificial intelligence as a basis for medical diagnostic systems can better identify the disease and make complementary treatment options.